Cancer of the rectum conservative treatments: Fundamentos oncológicos y anatomopatológicos. Indicaciones, táctica y técnica. - Bermúdez Villegas, Jorge; Falconi, Luis; Rompani, Omar; Veirano, Gustavo (Cirugía del Uruguay, 1985)
The authors review the literature regarding the Rectal Cancer Progression and Prognostic Factors to be considered from a clinicopathological point of view, concluding that, as long as a tumor is limited to the muscular wall of the rectum and either well or moderately differentiated, can be treated locally as conservative with results comparable to resection radical